Demography and age heaping: Solving Ireland's post-famine digit preference puzzle - Eoin McLaughlin; Christopher L. Colvin; Stuart Henderson (Queen's University Centre for Economic History (QUCEH), 2022)
Age heaping in Ireland worsened in the years after the Great Irish Famine, even as other measures of educational attainment improved. We show how demography can account for this seemingly conflicting pattern. Specifically, we argue that a greater propensity to emigrate typified the youngest segment (23-32-year-olds) used in conventional indices of digit preference. Quantification of heaping must be interpreted in light of an older underlying population which is more likely to heap. We propose how digit preference indices can adjust for such demographic change by introducing age standardisation.
Keywords: N33; J10; 330; age heaping; human capital; demography